2018
DOI: 10.22456/1679-9216.16335
|View full text |Cite
|
Sign up to set email alerts
|

Cortisol plasmático como indicador de estresse em colopexias laparoscópicas com implante de tela de polipropileno en cães

Abstract: A realização de cirurgias convencionais, mesmo com a utilização recomendada de fármacos analgésicos, geralmente está associada a um período de recuperação longo, além de causar estresse, dor e desconforto nos animais, dependendo do grau de invasão do procedimento. Considerando a crescente busca por métodos que minimizem o estresse cirúrgico em cães, reduzindo o período de recuperação pós-cirúrgico, o presente trabalho foi desenvolvido para avaliar a técnica de colopexia laparoscópica em relação aos níveis de c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 25 publications
0
4
2
Order By: Relevance
“…At T0 (before sedation/surgery), none of the animals were under any medication, and they had not experienced any painful stimulus. Therefore, the presence of high serum cortisol levels (μg/dL) at T0 suggests that they were displaying a response to stress that was not linked to any nociceptive stimulus (Freeman et al, 2010;Hekman et al, 2012;Hellyer et al, 2007;Michelsen et al, 2012;Zanella et al, 2009). Malm et al (2005b) and Horta et al (2015) assessed pain and stress in dogs subjected to OVH and mastectomy, respectively, and found no evidence of increased serum cortisol levels (μg/dL) before surgery, unlike the results presented in this study.…”
Section: Discussioncontrasting
confidence: 65%
See 2 more Smart Citations
“…At T0 (before sedation/surgery), none of the animals were under any medication, and they had not experienced any painful stimulus. Therefore, the presence of high serum cortisol levels (μg/dL) at T0 suggests that they were displaying a response to stress that was not linked to any nociceptive stimulus (Freeman et al, 2010;Hekman et al, 2012;Hellyer et al, 2007;Michelsen et al, 2012;Zanella et al, 2009). Malm et al (2005b) and Horta et al (2015) assessed pain and stress in dogs subjected to OVH and mastectomy, respectively, and found no evidence of increased serum cortisol levels (μg/dL) before surgery, unlike the results presented in this study.…”
Section: Discussioncontrasting
confidence: 65%
“…Although both groups showed increased glycemia (mg/ dL) in T4, the presence of hyperglycemic state observed only in the average of group 2 (OVH) was possibly due to nociceptive stimulation, intensifying the stress signals in these animals. Increased serum cortisol levels (μg/dL) are also known to lead to increased gluconeogenesis which, associated with increased circulating catecholamines, promotes insulin resistance, culminating in hyperglycemia (Hellyer et al, 2007;Horta et al, 2015;Zanella et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While there were no differences observed in platelet count among the surgical groups when compared with the control group (TE: 366,226 [29,477] cells/mm³, P = .059; VS: 421,945 [27,610] cells/mm³, P = .76; VI: 492,675 [29,055] cells/mm³, P = .75; and control: 456,256 [29,436] cells/mm³), the TE and VI groups did differ (P = .005; Figure 1A). In addition, there was no time effect on D0 (429,594 [24,256] cells/mm 3 ), D2 (459,862 [26,530] cells/mm 3 ), or D7 (413,372 [27,174] There was no difference in cortisol concentration between the treatment groups (TE: 3.87 [0.35] µg/dL; VS: 3.85 [0.31] µg/dL; VI: 3.27 [0.33] µg/dL; and control: 3.42 [0.37] µg/dL; P = .45). However, a difference in cortisol concentration was identified between D0 (3.97 [0.15] µg/dL) and D2 (3.24 [0.24] µg/dL; P = .02; Figure 1D).…”
Section: Resultsmentioning
confidence: 99%
“…When observing cardiorespiratory variables after the use of FLK in dogs undergoing arthroscopy, Belmonte et al (2013) found stability in the parameters, evidencing the analgesic action of FLK. Zanella et al (2009) and Rodrigues et al (2012) point out that cortisol is a great marker for assessing both trans-and postsurgical stress. However, several factors can influence the increase in cortisol in the body, including the anesthetic drug itself (Naddaf et al, 2014).…”
Section: Discussionmentioning
confidence: 99%